Branding - Power to Change Business Modality - Karki, Sarita Khadka (NCC Journal, 2018)
Branding refors to the strategic decisions and actions intended to create and maintain the firm's product or service concept in customer's mind. The form selects some of the key differentiation factors on which it has competitive advantage and establishes the image so that customers view the product or service as different. The projected image is crucial and what the firm does to the mind of customer's more important than what the firm does to the products. Nepal is ideally referred to as small market in terms of business generation, however more today Nepali market is flooded with international brands. But Nepal has extreme good brands and marketing practitioners as well they have been to create and establish amazing local brands. It also creates opportunities explain the growth of branding and marketing as a career option for the new generation. NCC Journal Vol. 3, No. 1, 2018, page: 176-180